Development of a multi-rotor VTOL UAV : computation of aerodynamics forces and moments using CFD - Tan, Dion Jin Yan (2018)
A VTOL model aircraft is analysed using CFD code. The model was first conceptually designed using a simplified design code XFLR5, and a full detailed assessment of the model is performed. Detailed mesh independence studies were performed and the results for longitudinal motion were obtained. Furthermore, the performance data (Power vs Velocity and Thrust vs Velocity) were deducted from steady level CFD analysis. The speed for minimum drag was also obtained from the CFD analysis. Results were also obtained for Cm vs α and results indicated that XFLR5 over predicted the location for the CG compared to the recommendation of CFD. A conclusion highlighting the recommendations made from CFD, and future work followed.